2017
DOI: 10.1007/s00420-017-1284-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of managers in addressing employees with musculoskeletal pain: a mixed methods study

Abstract: Purpose This study investigates management awareness of employee musculoskeletal pain and conditions that shape managers’ handling of employees with pain.Methods We used a mixed methods design including data from a questionnaire survey and focus group sessions. All employees and managers from seven nursing homes were invited to participate in the questionnaire survey and 327 employees (81%) and 31 managers (82%) responded. Employees were asked about their worst pain intensity the past month and managers were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…Studies have found that managers have limited awareness of employee pain and it is rarely openly discussed. 39 Managers habitually do not consider pain amongst employees a problem, 9 which is surprising given that a Danish study found that over…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have found that managers have limited awareness of employee pain and it is rarely openly discussed. 39 Managers habitually do not consider pain amongst employees a problem, 9 which is surprising given that a Danish study found that over…”
Section: Discussionmentioning
confidence: 99%
“…This may be particularly important because studies have shown that management behavior can significantly influence how an employee handles pain at work. 41–43 The Healthy Workplace Campaign was introduced to reduce workplace bullying in the United States, holding the employer accountable for an abusive work environment, which encourages employers to actively reduce hostility within the workplace. 44 Similar campaigns may hold the key to reducing the negative psychosocial association with chronic pain in the workplace.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors at both the individual, interpersonal and organisational levels may influence employee action when experiencing MSK problems. Managers play a key role in relation to workplace health [65,66] and management behaviour influences how an employee handles pain at work [67e69]. Providing possibilities for communication can influence whether an employee can continue working when experiencing pain [70], therefore, the importance of good communication between employers, staff and peers in supporting physical and mental health in the workplace has been recognised by the World Health Organisation (WHO) [71,72].…”
Section: Communication and Conversationsmentioning
confidence: 99%
“…Individuals with varying MSK conditions have explained that a supportive manager who allows time off for medical appointments, provides a stable working environment in terms of promoting positive workplace culture, and allowances for flexible working arrangements during disease flares, all facilitate worker retention [103,104]. It is important to note that flexible working arrangements extend beyond physical intervention; qualitative research suggests that employees with MSK conditions feel appreciative where employers initiate conversation about ways to facilitate worker productivity and retention [65,105].…”
Section: The Organisationmentioning
confidence: 99%